Primary Gastric Melanoma: A Rare Diagnostic Entity – A Case Report - Raza, Muhammad; Tariq, Ayesha; Raza, Ali (Biological and Clinical Sciences Research Journal, 2025)
Primary gastric melanoma is an extremely rare malignancy, with the majority of gastrointestinal melanomas being secondary to cutaneous lesions. Its diagnosis is challenging due to nonspecific symptoms and the need for histopathological confirmation. Case Presentation: We report the case of a 55-year-old male presenting with a year-long history of hematemesis, vague chest discomfort, epigastric pain, fatigue, melena, and significant weight loss. Endoscopic examination revealed multiple pigmented polypoid masses in the stomach. Biopsy and immunohistochemistry confirmed malignant melanoma. No cutaneous, ocular, or anorectal primary lesion was identified. The patient underwent total gastrectomy with Roux-en-Y esophagojejunostomy and regional lymphadenectomy. Conclusion: Primary gastric melanoma should be considered in the differential diagnosis of upper gastrointestinal bleeding, mainly when pigmented lesions are observed. Early diagnosis and surgical resection are critical, although prognosis remains poor due to its aggressive behavior and early metastatic potential.